Monitoring the differences in swimming skills development among men and women medalists at the 21st World Aquatics Championships - Doha 2024, Qatar - Ganchar, I.; Ganchar, O.; Ciorba, C.; Medynskyi, S.; Protsenko, A.; Tsybulska, V.; Kyriienko, O.; Sukhanova, H.; Potop, V. (Journal of Physical Education and Sport, 2025)
Aim: This study aimed to identify differences in the parameters of swimming skills development among prize-winning swimmers of varying ages and genders, based on the results of the 21st World Aquatics Championships, held on February 2--18, 2024, in Doha, Qatar. Material: Achievements of 111 men and 111 women prize-winning swimmers were analyzed across 50 events in both sport and marathon swimming. Methods: The study used a theoretical analysis of the specialized literature and practical experience, along with a preliminary experiment, generalization of documentary materials and mathematical statistics. Results: A total of 31 countries won medals at the 21st World Aquatics Championships (Doha 2024). The USA recorded the most successful performances with 20 medals in swimming, followed by Australia with 16 medals in swimming and 2 marathon swimming medals, Italy (12+2), China (11), the Netherlands (6+2), Great Britain (7+1), Canada (7), Germany (6), France (2+3) and New Zealand (4). Countries in the second tier of rankings included Sweden (4 medals), South Korea (3), Portugal (2+1), Spain (2+1), Hong Kong (3), Hungary (1+2), Poland (3), Ireland (2), Lithuania (2), Japan (2) and Austria (2). Each one of the remaining countries, including Ukraine, Switzerland, Denmark, Israel, South Africa, Greece, Belarus, Bosnia and Herzegovina, Egypt and Brazil, won a single medal. Age-related differences were identified across distances. Men had a 1-7-year age advantage at seven distances, while no age difference was observed at five distances. Women had a 1-6-year age advantage at 13 distances. The overall average age of both groups was similar (men = 24.24 ± 1.88 years, women = 24.44 ± 2.04 years; t = 0.747; p > 0.05). Regarding swimming speed, the largest differences between men and women were observed in relay events (0.21 m/s), short-distance freestyle (50 m: 0.215 m/s; 100 m: 0.196 m/s), backstroke (0.196 m/s), butterfly (0.176 m/s) and breaststroke (0.176 m/s). The smallest differences were noted in long-distance freestyle events (400-800-1500 m: 0.135 m/s) and mixed relays (4×100 m freestyle and medley: 0.12 m/s). The overall difference in average swimming speed across all events was 0.16 m/s (men = 1.84 ± 0.16 m/s; women = 1.68 ± 0.14 m/s; t = 2.225; p < 0.05). Conclusion: The 21st World Swimming Championships highlighted the dominance of top-performing countries, with the USA, Australia and Italy leading in both quality and quantity of medals. Gender-based analysis revealed significant disparities in average swimming speed, particularly at shorter distances and relay events, with men demonstrating consistently higher speeds. However, smaller differences were observed in long-distance and mixed relay events, indicating the decreasing performance gap in endurance-based disciplines. So, these findings underscore the continuous evolution of competitive swimming performance across genders and distances.